Strategi Media Massa Lokal Pelita Karawang dalam Menghadapi Doxing - Setyawati, Mala; Anzelina, Rahmah; Jamil, Syakira Nasywa (Universitas Singaperbangsa Karawang, 2023)
In today's era of technological development, information can spread quickly and uncontrollably. The consequence of the rapid spread of information is the disruption of private information by irresponsible parties. There is one phenomenon called doxing. Doxing is the digging up and dissemination of a person's personal information to the internet without permission with specific purposes such as intimidating, humiliating, threatening, or stalking the victim and even punishing the targeted person. Through qualitative methods, research is more subjective perspective. According to Sugiyono (2018: 213). Doxing can have an impact on journalists. Educating readers on how to consume information wisely and emphasizing high journalistic ethics and standards can help reduce doxing incidents. Full support for press freedom and protection of journalists from external threats such as doxing should also be a major focus for the government and related institutions